Working memory in preterm‐born adults: Load‐dependent compensatory activity of the posterior default mode network. Issue 3 (21st November 2014) - Daamen, Marcel; Bäuml, Josef G.; Scheef, Lukas; Sorg, Christian; Busch, Barbara; Baumann, Nicole; Bartmann, Peter; Wolke, Dieter; Wohlschläger, Afra; Boecker, Henning
Abstract Premature birth is associated with an increased risk of cognitive performance deficits that are dependent on working memory (WM) load in childhood. Less clear is whether preterm‐born adults show similar WM impairments, or develop compensatory brain mechanisms that help to overcome prematurity‐related functional deficits, for example, by a workload‐dependent over‐recruitment of WM‐typical areas, and/or engagement of alternative brain networks. In this functional magnetic resonance imaging study, 73 adults born very preterm and/or with very low birth weight (VP/VLBW) and 73 term‐born controls (CON, mean age: 26.5 years) performed a verbal N‐Back paradigm with varying workload (0‐back, 1‐back, 2‐back). Generally, both groups showed similar performance accuracy and task‐typical patterns of brain activations (especially in fronto‐cingulo‐parietal, thalamic, and cerebellar areas) and deactivations (especially in mesial frontal and parietal aspects of the default mode network [DMN]). However, VP/VLBW adults showed significantly stronger deactivations (P < 0.05, cluster‐level corrected) than CON in posterior DMN regions, including right ventral precuneus, and right parahippocampal areas (with adjacent cerebellar areas), which were specific for the most demanding 2‐back condition. Consistent with a workload‐dependent effect, VP/VLBW adults with stronger deactivations (1‐back > 2‐back) in the parahippocampal/cerebellar cluster also presented a greater slowing of response latencies with increasing WM load (2‐back > 1‐back), indicative of higher effort. In conclusion, VP/VLBW adults recruited similar anatomical networks as controls during N‐back performance, but showed an enhanced suppression of posterior DMN regions during higher workload, which may reflect a temporary suppression of stimulus‐independent thoughts that helps to maintain adequate task performance with increasing attentional demands. Hum Brain Mapp 36:1121–1137, 2015.© 2014 Wiley Periodicals, Inc.